ABOUT THE PECULIARITIES OF THE SOCIAL MOOD OF YOUNG PEOPLE - A.Abdullazizov (Galaxy International Interdisciplinary Research Journal, 2022)
The article talks about the social well-being of young people and the factors influencing it, revealing their reaction to changes and determining in which direction society should act in order for all these changes to be positive. An attempt was made to show that social well-being is a multifaceted indicator that is associated with such concepts as well-being, life satisfaction, public mood and happiness.